Pengaruh Kompensasi, Motivasi, dan Semangat Kerja Terhadap Kinerja Karyawan Pada CV. Harapan Baru Bekasi - Adzansyah Adzansyah; Sugeng Suroso; Supriyanto Supriyanto (CV. KAMPUSA AKADEMIK PUBLISHING, 2025)
This research aims to determine the effect of compensation, motivation, and morale on the performance of CV. Harapan Baru Bekasi. The type of research used in this research is quantitative research. Where the object is the employees of CV. Harapan Baru Bekasi. The sampling technique uses a non-probability sampling method with a saturated sample technique (census), namely all members of the population are used as samples, a total of 50 employees of CV. Harapan Baru Bekasi. The data analysis method uses multiple linear regression. The results of this study indicate that (1) compensation has a positive and significant effect on the performance employees of CV. Harapan Baru Bekasi (2) motivation has a positive and significant effect on the performance employees of CV. Harapan Baru Bekasi (3) morale has a positive and significant effect on the performance employees of CV. Harapan Baru Bekasi and (4) compensation, motivation, and morale simultaneously have a significant effect on the performance employees of CV. Harapan Baru Bekasi.